The Influence of Learning Approeach and Eye-Hand Coordination on The Learning Outcomes of Mini Volleyball Passing Skill (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this research was to find out the influence of learning approach and eye-hand coordination on students learning outcomes of mini volley ball passing skills at Bulungan Elementary School. This research used an experimental method with the 2x2 factorial design. Research samples were 70 students who were taken by purposive sampling technique. The instrument for passing was Braddy Wall Volley ball Test from Johnson BL and Nelson JK, eye-hand coordination by throwing tennis balls on a wall that had been targeted by Ismaryati in Tatag Efendi. The technique used to analyze data is used in two ways with a computer program. The results showed there was a difference in the effect of the drill learning approach and playing on the results of learning the skills of playing mini volleyball, there was a difference in the learning outcomes of mini volley ball skills between students who have high and low eye-hand coordination, and there was interaction between learning approaches and eye-hand coordination on the results of learning skills playing mini volleyball. The conclusion of this research was playing approach-teaching had a better influence on students learning outcomes of mini volley ball passing skills at Bulungan Elementary School. Based on the results of the research, playing approach - teaching is can be used as a method to improve students' passing skills learning.